Design and simulation of single quantum well LED - حنكة, أيمن; سخري, محمد حشاني; مصباحي, نضال (University of El-Oued, 2021)
"Abstract Lighting is an essential component of economic activity in our modern society. It represents about 25% of the total electrical energy consumption globally. However, these lighting consume a lot of electricity produced mostly by polluting thermal power plants. Incandescent lamp has been the dominant component in lighting for over a hundred years despite an efficiency of only 17 lumens per watt .Today a new source of lighting is available that reduces the consumption of electricity and thus the production of greenhouse gases. Light-emitting diodes (LEDs), their energy efficiency, reliability and very long life can potentially overcome previous issues. Diverse types and structures have been previously studied in literature. In our work, single quantum well (SQW) LED based on InGaN material using Silvaco-Atlas software has been simulated and studied. The simulation results demonstrate that the device performance is considerably enhanced by the use SQW LED compared to that of standard LED. In addition, the effect of well-width on SQW design has been examined. Accordingly, the value of 47558 A/cm2 is achieved in case of 2nm well-width, and it is better than 3nm and 2nm well-width. Clearly, the well-width of 2nm provides better performance compared to that of 3nm and 4nm. Keywords: LED, single quantum well, IV characteristics, Silvaco-Atlas software. " "الملخص الإضاءة عنصر أساسي للنشاط الاقتصادي في مجتمعنا الحديث. يمثل حوالي 25٪ من إجمالي استهلاك الطاقة الكهربائية على مستوى العالم. ومع ذلك ، فإن هذه الإضاءة تستهلك الكثير من الكهرباء المنتجة في الغالب عن طريق تلويث محطات الطاقة الحرارية. لقد كان المصباح المتوهج هو المكون السائد في الإضاءة لأكثر من مائة عام على الرغم من كفاءة 17 لومن فقط لكل واط ، واليوم يتوفر مصدر جديد للإضاءة يقلل من استهلاك الكهرباء وبالتالي إنتاج الغازات المسببة للاحتباس الحراري. يمكن أن تتغلب الثنائيات الباعثة للضوء (LED) وكفاءتها في استخدام الطاقة وموثوقيتها وعمرها الطويل جدًا على المشكلات السابقة. تمت دراسة أنواع وهياكل متنوعة مسبقًا في الأدب. في عملنا ، تمت محاكاة ودراسة البئر الكمي الفردي (SQW) المستند إلى مادة InGaN باستخدام برنامج Silvaco-Atlas. تظهر نتائج المحاكاة أن أداء الجهاز تم تحسينه بشكل كبير من خلال استخدام SQW LED مقارنة بأداء LED القياسي. بالإضافة إلى ذلك ، تم فحص تأثير عرض البئر على تصميم SQW. وفقًا لذلك ، يتم تحقيق قيمة 47558 ​​أمبير / سم 2 في حالة عرض البئر 2 نانومتر ، وهو أفضل من عرض جيد 3 نانومتر و 2 نانومتر. من الواضح أن العرض الجيد الذي يبلغ 2 نانومتر يوفر أداءً أفضل مقارنةً بأداء 3 نانومتر و 4 نانومتر. الكلمات الرئيسية: LED ، بئر كم واحد ، خصائص IV ، برنامج Silvaco-Atlas."
Systeme de telecommunication مذكرة ماستر تخصص
Keywords: "LIST OF SYMBOLS AND ABBREVIATIONS LED Light-Emitting Diode OLED Organic Light-Emitting Diode AMOLED Active Matrix OLED EQE External Quantum Efficiency SCLC Space-Charge-Limited Current HOMO Highest Occupied Molecular Orbital LUMO Lowest Unoccupied Molecular Orbital PTPB polytetraphenylbenzidine MO metal–organic FN Fowler Nordheim HTL Hole Transporting Layer ETL Electron Transporting Layer EML Emissive Layer SSL solid-state lighting FPDs flat-panel displays IESNA Illuminating Engineering Society of North America GaN gallium-nitride GaAsP gallium-arsenic-phosphide InGaN indium-gallium-nitride HID high-intensity discharge "; "قائمة الرموز والاختصارات الصمام الثنائي الباعث للضوء الصمام الثنائي العضوي الباعث للضوء OLED AMOLED Active Matrix OLED كفاءة الكم الخارجية EQE SCLC Space-Charge-Limited Current HOMO أعلى مداري جزيئي مشغول LUMO المداري الجزيئي الأدنى غير المشغول PTPB بوليتيترافينيل بنزيدين MO معدن - عضوي إف إن فاولر نوردهايم طبقة نقل HTL Hole طبقة نقل الإلكترون ETL طبقة EML Emissive إضاءة الحالة الصلبة SSL شاشات مسطحة FPDs جمعية هندسة الإضاءة IESNA من أمريكا الشمالية نيتريد الجاليوم GaAsP الغاليوم - الزرنيخ - فوسفيد إنديوم غاليوم نيتريد InGaN تفريغ عالي الكثافة"